Dynamic supply chain design: a Delphi study of drivers and barriers. Issue 22 (17th November 2017) - Krægpøth, Thorsten; Stentoft, Jan; Jensen, Jesper Kronborg
Abstract : Supply chain management has both in academia and practice proven its important role to sustain and further develop companies' competitive advantages. This is with initiatives that focus on cost-efficiencies and turnover improvement. During the last two decades, companies have faced complexity in their supply chains currently with increased global operations. The dynamic business environment forces companies to secure a competitive (re-) design of their supply chains. This paper seeks to advance the understanding on the drivers and barriers for such designs. In total, 39 experts (30 from industrial enterprises, 4 senior supply chain consultants and 5 supply chain management professors) have participated in a four-step Delphi study and have identified main drivers for dynamic supply chain design as being cost reduction, delivery reliability and change in demand for agility. The main barriers are identified as forecasting being too weak, supply chain complexity and product portfolio complexity. In addition, an explorative factor analysis has been carried out to identify how drivers and barriers can be grouped together. Finally, the paper compares the drivers and barriers underlining different competitive strategies.